Survey of various query suggestion system (International Journal of Engineering and Computer Science, 2014)
Now a days, Internet has become essential for banking, education, business and many more applications. Users search information on the web using search engines by clicking on hyperlinks or via keyword queries. So to develop user search intent application is challenging, satisfying increased expectations and diverse needs of user. In this paper, we will survey the various techniques used for query suggestion, personalization and FAQ identification. We will review query suggestion by considering query contents, document clicks, query frequency and semantic features. Thus, by automating the optimization process of searching on web; we can minimize user efforts; maximize user satisfaction for getting desired search.